Cross-Sectional Survey on BNT162b2 mRNA COVID-19 Vaccine Serious Adverse Events in Children 5 to 11 Years of Age: A Monocentric Experience - Silvia Bloise; Alessia Marcellino; Beatrice Frasacco; Pietro Gizzone; Claudia Proietti Ciolli; Vanessa Martucci; Mariateresa Sanseviero; Emanuela Del Giudice; Flavia Ventriglia; Riccardo Lubrano (Vaccines, 2022)
Objective: Our aim was to evaluate the safety of COVID-19 vaccine in children resident in the Latina Local Health Authority. Methods: We conducted a telephone survey among children aged 5–11 years receiving BNT162b2 mRNA COVID-19 vaccine between December 15 and 21. The main outcomes included the presence of allergic reactions or anaphylaxis, adverse events after 24–48 h, 7 and 20 days of taking the first and second doses of medications, and documented SARS-CoV-2 infection after vaccination. The information obtained was automatically linked to a spreadsheet and analyzed. Results: 569 children were enrolled. The mean age was 114 ± 4.24 months; there were 251 males in the study. The vaccine showed a favorable safety profile; no anaphylaxis or serious adverse events were reported. The most common symptoms both after the first and second dose were injection site reactions, asthenia, and headache. Injection site reactions were more frequent after the first dose (p = 0.01), while systemic symptoms were more frequent after the second dose (p = 0.022). These symptoms were more frequent in patients with comorbidities (p = 0.0159). Conclusion: Our findings confirm the safety of COVID-19 vaccine in children younger 11 years and could be useful to promote its diffusion in pediatric ages in order to achieve “herd immunity” and prevent the virus’s circulation.